Study on the relationship between insomnia disorder, PET/CT, and gut microbiota in patients with Alzheimer’s disease - Kang, Jian; Chen, Jianwen; Li, Peixue; Zhao, Shiqi; Jing, Fangfang; Xie, Jinghui; Dong, Chunbo (Frontiers in Neurology, 2025)
ObjectivePrevious studies on Alzheimer’s disease (AD) have focused on the relationships between brain pathology and gut microbiota, brain pathology and sleep, and sleep and gut microbiota, but no study has explored the relationship between these three factors. Therefore, we integrated these three factors into a unified framework and aimed to provide a reference for treating insomnia disorders (ID) in patients with AD.Patients/methodsThe 65 patients diagnosed with AD were categorized into ID group (n = 30) and non-ID group (n = 35) according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition. Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality. 18F-fluorodeoxyglucose (FDG)-positron emission tomography (PET) and 18F-florbetapir (AV45)-PET scan were performed. Fecal samples were analyses using 16S rRNA amplicon sequencing. Basic data, PET, and gut microbiota were compared between the ID and non-ID groups. Finally, the relationships among the data, with differences including PSQI, were analyses. All p-values were corrected using the False Discovery Rate (FDR) method to obtain q-values.ResultsData with significant differences (p < 0.05 or q < 0.05) included PSQI, left middle frontal cortex-FDG, left Broca’s area-FDG, right thalamus (rTh)-FDG, left thalamus (lTh)-FDG, Roseburia, Prevotella 7, and Bifidobacterium. However, no differences were found between groups in AV45-PET. In the ID group, PSQI scores were significantly correlated with rTh-FDG (r = −0.612, q < 0.05), lTh-FDG (r = −0.585, q < 0.05), and Bifidobacterium (r = −0.637, q < 0.05). Partial least squares structural equation modeling revealed that Thalamic-FDG exerted a partial mediating effect in the association between Bifidobacterium and PSQI scores.ConclusionIn AD patients with ID, there may be both a direct and an indirect association between Bifidobacterium and sleep quality, with thalamic glucose metabolism mediating the indirect association, indicating that treatments aimed at enhancing brain metabolism and probiotic supplementation may improve sleep quality in this population.